Félix d'Herelle and the origins of molecular biology - Summers, William C. (Yale University Press, 1999)
A self-taught scientist determined to bring science out of the laboratory and into the practical arena, French-Canadian Felix d'Herelle (1873-1949) made history in two different fields of biology. Not only was he first to demonstrate the use and application of bacteria for biological control of insect pests, he also became a seminal figure in the history of molecular biology. This engaging book is the first full biography of d'Herelle, a complex figure who emulated Louis Pasteur and influenced the course of twentieth-century biology, yet remained a controversial outsider to the scientific community. Drawing on family papers, archival sources, interviews, and d'Herelle's published and unpublished writings, Dr. William C. Summers tells the fascinating story of the scientist's life and the work that took him around the globe.